Jargon in Communication Pattern of Traders and Buyers at Traditional Market Karya Kasih Medan Johor.: Array - Elsera, Cindy; Ariffudin, H (Universitas Harapan Medan, 2022)
This research aimed to discuss about the form and the function of jargon used by traders and buyers at traditional market Karya Kasih Medan Johor in communication. The data of this research were taken from utterance of traders and buyers in Traditional Market. This research used qualitative method and the sociolinguistics approach to analyzed the data. To get the result of this research requires several steps, the steps are observation the location,identifying the jargon, clssifiyng the form of jargon and function of jargon, and the last dominat form of jargon. The result of this research were found(3) Acronym, ( 2 ) Abbreviation, (16) Word, (2) Code, and (4) foreign language and the function of jargon classified 4 functions a) as a suggestion of getting acquainted or bonding (b) means of producing certain information (c) for buying and selling or transaction (d) a means to show membership of social identity. The researcher used observation sheet and interview sheet as the instrument to get the valid data. Based on the result, word form was the most frequent that occurred in their communication. The buying and selling for transaction were the most frequent that occurred among group members. The research concluded that traders and buyers used most jargon words in traditional market area.